Comparação das características e medidas ultrassonográficas do rim entre cães e gatos filhotes - Charas Dos Santos, Ivan Felismino [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Sartor, Raquel (My University, 2015)
The ultrasound exam is an effective and low cost method of image diagnosis, which helps in identification of kidneys diseases. It is necessary to establish normality standards for ultrassonography renal characteristics and dimensions and thickness of cortical and medullar regions in healthy animals, which can be used for identification of renal alterations. The study aimed to analyze and compare the ultrasound characteristics and dimensions of the kidneys, evaluating the significant difference in renal measurement between healthy puppies and kittens, and establishing standards of normality and reference values. Fifteen healthy puppies with mean weight of 3 kg (3 kg - 4 kg), and fifteen healthy kittens with means weight of 2 kg (1 kg - 3 kg), cross breed and age between five and six months were included in this study. All animals underwent renal ultrasound for visualization of internal characteristics and assess renal length, cortical thickness, medullar thickness and corticomedullary ratio. The renal margin was not observed in puppies but was observed in 50% of kittens. The renal cortex in puppies was visualized with similar echogenicity to the spleen. The ultrasound measurements between the left and right kidney in puppies and kittens have showed no significant difference. The ultrasound measurements of kidneys between puppies and kittens showed a significant difference. The puppies kidneys, right and left, tend to be bigger in length (5.18 ± 0.01 cm and 5.16 ± 0.01 cm), cortical thickness (0.74 ± 0.02 cm and 0.74 ± 0.01 cm), medullar thickness (0.74 ± 0.02 cm and 0.74 ± 0.01 cm) in relation to renal length (2.98 ± 0.01 cm and 2.92 ± 0.02 cm), cortical thickness (0.33 ± 0.01 cm and 0.32 ± 0.01 cm), medullar thickness (0.32 ± 0.02 cm and 0.31 ± 0.02 cm) in kittens. However, the corticomedullary ratio (PCM) was similar in both groups.
Comparison of renal ultrasonographic characteristics and measurements between puppies and kittens
Keywords: Abdomen; Kidney; Measurements; Small animals; Ultrasonography